Optical control of a resonant tunneling diode microwave-photonic oscillator - Romeira, B.; Figueiredo, J.; Ironside, Charlie; Kelly, A.; Slight, T. (2010)
We report on optical injection-locking of a microwave-photonic oscillator based on the integration of a resonant tunneling diode optical waveguide photodetector with a communication laser diode. The oscillator locking was achieved with in-fiber optical powers as low as 0.2 mW, and locking ranges up to 23.8 MHz for in-fiber optical power of few milliwatts and with phase-noise suppression below -110 dBc/Hz at 10-kHz frequency offset from the center frequency. The circuit's dynamics are well described as an optically controlled Linard oscillator. © 2006 IEEE.